O USO PEDAGÓGICO DO PODCAST E FORMAÇÃO INICIAL DO PROFESSOR: MUDANÇAS DE PARADIGMA EDUCACIONAL - Silva, Weslley Kozlik (2017)
This work made possible the understanding of the Podcast and its pedagogical use in the initial formation of teachers of the Pedagogy course. During much of the history, technology and education had their development in parallel, starting with orality, later on through the emergence of writing, later for the formation of books and the first masters, followed by the systematization of teaching in schools, which permeated diverse cultures, from Egypt to the present day, with different teaching methods. However, at a certain moment in this timeline, technology and education have stopped developing in parallel, especially in Brazil, which in a way demonstrates a fragility in education, since technology has accompanied and helped in the development of society and, once that education no longer has this parallel with technology, it is possible to understand that education and society can be disorganized in many ways. Therefore, in order to narrow the relationship between technology and education, and consequently education and society, this work aims to verify the use of a technological tool called Podcast as a possibility to change the educational paradigm in initial teacher training, as well as research on the temporal context from orality, the emergence of writing and other technologies as educational strategies; to ascertain the educational paradigm in which the teachers in initial formation meet; prepare and apply a course to instrumentalize the production and use of Podcast in education; and to organize and analyze the results obtained through an extension course, questionnaires and other data collection instruments used with the teachers in initial formation. These objectives can be achieved through a methodology of Phenomenological-hermeneutic characteristic, which enables the analysis of the discourse of the teachers in initial formation in their answers to the questionnaires. The results of the research were categorized into characteristics of the context of the participants (obtained through the initial questionnaire), mediation of the Podcast instrumentalization course and analysis of the final questionnaire. The analysis of the research participants' answers indicated that it was possible to generate changes in the educational paradigm of these, since they pointed to approximations with the emergent educational paradigm after the instrumentalization of the technological tool. Thus, a rapprochement with the development of society. However, it is understood that only Podcast is not enough to generate and maintain paradigmatic changes. It is necessary that all educationrelated partners take advantage of this situation so that the changes are indeed effective.